Applications and Challenges of Artificial Intelligence in the Future of Art Education - Ke, Mu Fan (Pacific International Journal, 2023)
With the rise of the digital era, the implementation of artificial intelligence (AI) technology in the realm of education is garnering increased attention. Art education, which centers on creativity and expression, is no exception to the influence of AI. However, several challenges must be addressed in the prospective use of AI in university art education. Firstly, privacy protection emerges as a crucial issue. Educational institutions must establish stringent privacy policies to safeguard student data, ensuring its security and confidentiality while adhering to relevant laws and regulations. By adopting transparent data collection and usage standards, trust among students and parents can be cultivated, thereby enhancing the acceptance of AI technologies in fine arts education. Secondly, ensuring the reliability and accuracy of AI tools is imperative. Collaborative efforts between educational institutions and technology vendors are necessary to guarantee the quality and efficacy of AI algorithms and models. Regular testing and evaluation can identify and rectify potential issues, thereby bolstering the tools' reliability. Simultaneously, educators should receive comprehensive training and professional development to comprehensively understand and effectively employ AI tools. Furthermore, educational institutions and educators should actively engage in the development and research of AI technologies. Collaborative partnerships with technology developers can yield AI tools and applications tailored to art education. Through continuous collaboration and feedback loops, these tools can be refined and optimized to better align with educational requirements. Lastly, educators should maintain a rational and critical perspective concerning AI technologies. While AI can provide valuable teaching aids, it should not supplant the role and significance of human educators. Educators must continue leveraging their expertise and experience to guide students' creativity, foster critical thinking, and nurture artistic expression. This paper concludes that the potential for AI in the future of university art education is substantial, albeit accompanied by challenges. By actively addressing concerns related to privacy protection, reliability, and educational engagement, AI can play a positive role in art education. Collaboration among educational institutions, educators, and technology developers is pivotal in realizing this vision, thereby promoting the sustainable development and effective application of AI in art education.